GE_GERICHTE C/1999/2016 vom 16. Dezember 2016 - GE Cour de justice (2016)
PROTECTION DE L'UNION CONJUGALE ; OBLIGATION D'ENTRETIEN ; CONJOINT ; FRAIS(EN GÉNÉRAL) ; REVENU HYPOTHÉTIQUE | CC.163; CC.176.1.1;